CBT Group Counseling with Stress Inoculation Training and Thought-Stopping Techniques to Improve Students’ Academic Hardiness - Gustanti, Ira; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2019)
The purpose of this study was to analyze CBT group counseling with stress inoculation training and thought to stop techniques to improve students’ academic hardiness. Meanwhile, the design used was pre-test and multiple post-test by involving 16 subjects of the study chosen by using purposive sampling from total 280 students of Public Senior High School 1 Godong. Their data were collected though the Hardiness Scale. Furthermore, repeated measure anova analysis showed that CBT group counseling with stress inoculation training and thought stopping techniques was effective to improve students’ academic hardiness. These findings assert that CBT group counseling with stress inoculation training and thought stopping techniques is effective to improve students’ academic hardiness.